Endoscopic sleeve gastroplasty, laparoscopic sleeve gastrectomy, and laparoscopic greater curve plication: do they differ at 2 years? - Lopez-Nava, Gontrand; Asokkumar, Ravishankar; Bautista-Castaño, Inmaculada; Laster, Janese; Negi, Anuradha; Fook-Chong, Stephanie; Nebreda Duran, Javier; Espinett Coll, Eduard; Gebelli, Jordi Pujol; Garcia Ruiz de Gordejuela, Amador (Endoscopy, 2020)
Background Endoscopic sleeve gastroplasty (ESG) is an effective treatment option for obesity. However, data comparing its efficacy to bariatric surgery are scarce. We aimed to compare the effectiveness and safety of ESG with laparoscopic sleeve gastrectomy (LSG) and laparoscopic greater curve plication (LGCP) at 2 years.Methods We reviewed 353 patient records and identified 296 patients who underwent ESG (n = 199), LSG (n = 61), and LGCP (n = 36) at four centers in Spain between 2014 and 2016. We compared their total body weight loss (%TBWL) and safety over 2 years. A linear mixed model (LMM) was used to analyze repeated measures of weight loss outcomes at 6, 12, 18, and 24 months to compare the three procedures. Results Among the 296 patients, 210 (ESG 135, LSG 43, LGCP 32) completed 1 year of follow-up and 102 (ESG 46, LSG 34, LGCP 22) reached 2 years. Their mean (standard deviation [SD]) body mass index (BMI) was 39.6 (4.8) kg/m2. There were no differences in age, sex, or BMI between the groups. In LMM analysis, adjusting for age, sex, and initial BMI, we found ESG had a significantly lower TBWL, %TBWL, and BMI decline compared with LSG and LGCP at all time points (P = 0.001). The adjusted mean %TBWL at 2 years for ESG, LSG, and LGCP were 18.5 %, 28.3 %, and 26.9 %, respectively. However, ESG, when compared with LSG and LGCP, had a shorter inpatient stay (1 vs. 3 vs. 3 days; P < 0.001) and lower complication rate (0.5 % vs. 4.9 % vs. 8.3 %; P = 0.006).Conclusion All three procedures induced significant weight loss in obese patients. Although the weight loss was lower with ESG compared with other techniques, it displayed a better safety profile and shorter hospital stay.